The Effectiveness of a Tomini Bay Maritime-Contextualized E-Module on Reaction Rate in Improving Students’ Scientific Literacy - Erga Kurniawati; Thayban Thayban; Haris Munandar (Universitas Negeri Gorontalo, 2025)
This study aimed to evaluate the effectiveness of a maritime-based e-module contextualized to Teluk Tomini in improving students’ scientific literacy on the topic of reaction rates at SMA Negeri 1 Suwawa. A quasi-experimental method employing a posttest-only control group design was utilized. The study involved an experimental group, which was instructed using the maritime-based e-module, and a control group, which received instruction through a conventional e-module. The findings indicate that students who learned using the Tomini Bay maritime-based e-module demonstrated significantly higher levels of scientific literacy compared to those who were taught using the conventional approach. The mean scientific literacy score of the experimental group reached 22.26, substantially exceeding that of the control group, which obtained a mean score of 11.56. Statistical analysis using One-Way ANOVA confirmed a significant difference between the two groups. The study concludes that the implementation of a maritime-based e-module is effective in enhancing students’ scientific literacy, increasing student engagement, and facilitating the comprehension of abstract concepts such as reaction rates. Furthermore, the module promotes awareness of local environmental sustainability, thereby integrating contextual relevance with scientific understanding.